2008
DOI: 10.1016/j.theochem.2008.01.004
|View full text |Cite
|
Sign up to set email alerts
|

TD-DFT investigation on the electronic spectra of novel N-methylmaleimides linked with indolizine ring system

Abstract: The major electronic absorption features in visible region were computationally investigated for a series of novel N-methylmaleimide derivatives. The newly synthesized compounds through the reaction of indolizines with N-methylmaleimides exhibited their maxima ranging 587-634 nm in solution at room temperature. Time dependent density functional theory (TD-DFT) calculations were performed in order to elucidate their structure-color relationship, as well as to assess its performance using a variety of exchange-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…Table II shows the corresponding electronic excitation energies (E exc ), their oscillator strengths (f), and the orbital transitions most markedly contributing to the excitation in each case. Consistent with previous results [37,55,56], the E exc values provided by the B3LYP functional were higher than those obtained with the HCTH functional.…”
Section: Theoretical and Experimental Study Of The Excitation Energiesupporting
confidence: 91%
“…Table II shows the corresponding electronic excitation energies (E exc ), their oscillator strengths (f), and the orbital transitions most markedly contributing to the excitation in each case. Consistent with previous results [37,55,56], the E exc values provided by the B3LYP functional were higher than those obtained with the HCTH functional.…”
Section: Theoretical and Experimental Study Of The Excitation Energiesupporting
confidence: 91%
“…Slight influence of the correlation term to λ max was indicated with the gap between B3LYP and B3PW91 being only 2 nm. These XC-functional influences are in a qualitative agreement to our previous TDDFT results [13]. The optimized TDDFT scheme above-mentioned characterized the low-lying six singlet excited states for 3a, as in Table 3.…”
Section: Geometry Basis Set (Dft)supporting
confidence: 89%
“…Using the other functionals, the amplitude of λ max displacement is severely large; BLYP-, VSXC-, and HCTH-predicated peaks showed large deviations particularly for 3c and 3d. In our previous TDDFT study [13], we found some specific features and limitations of theoretical λ max for the newly prepared maleimide derivatives, where the molecules with large twist angle showed better λ max agreement owing to efficient charge separation between the two moieties while PBE0 and MPW91PW91 gave better λ max agreements than other functionals and the agreements worsen for planar compounds. All types of XC-fuctionals employed failed to reproduce hypsochromic shift of 3c and 3d in comparison with 3a and 3b.…”
Section: Other Maleimide Derivativesmentioning
confidence: 85%
“…Consistent with previous results, E exc values provided by the B3LYP functional are higher than those obtained from the HCTH functional. 17,18,42,43 Tables 6 and 7 show for each 3-HPY and PM form the computed electronic excitation energies (E exc ), their oscillator strengths (f) and the orbital transitions most markedly contributing to the excitation in each case. E exc and f values are compared with their experimental counterparts determined by UV-vis spectra deconvolution techniques.…”
Section: Td-dft Calculations Predict Accurately the Excitation Energi...mentioning
confidence: 99%